1999
DOI: 10.1161/01.str.30.1.140
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Experimental Vasospasm in Rats With the Periadventitial Administration of Ibuprofen Using Controlled-Release Polymers

Abstract: Background and Purpose-The chronic phase of vasospasm after an aneurysmal subarachnoid hemorrhage may be mediated in part by early leukocyte-endothelial cell interactions. Ibuprofen is an anti-inflammatory agent that inhibits expression of certain cell adhesion molecules and therefore disrupts leukocyte-endothelial cell interactions. Its systemic administration, however, has dose-limiting side effects. We evaluated the effect of the periadventitial delivery of ibuprofen using controlled-release polymers in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
44
0

Year Published

2001
2001
2013
2013

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 86 publications
(47 citation statements)
references
References 47 publications
3
44
0
Order By: Relevance
“…5,7,8 In addition, the administration of ibuprofen, which decreases intercellular adhesion molecule-l expression, results in decreased macrophage/neutrophil transendothelial migration and subsequently less vasospasm. 4,6 Hp is a serum protein that limits the extent of inflammation following a hemorrhagic event. 18,19 After a hemorrhage, blood is extravasated into the interstitial space, leading to the breakdown of erythrocytes and subsequent release of Hgb.…”
Section: Discussionmentioning
confidence: 99%
“…5,7,8 In addition, the administration of ibuprofen, which decreases intercellular adhesion molecule-l expression, results in decreased macrophage/neutrophil transendothelial migration and subsequently less vasospasm. 4,6 Hp is a serum protein that limits the extent of inflammation following a hemorrhagic event. 18,19 After a hemorrhage, blood is extravasated into the interstitial space, leading to the breakdown of erythrocytes and subsequent release of Hgb.…”
Section: Discussionmentioning
confidence: 99%
“…Another smaller study concluded, on the basis of 50 patients given aspirin suppositories (100 mg) for 21 days after the surgery for aneurysm clipping (at 4 days maximum), that there could be some longterm benefit in the treatment, but a larger trial was necessary to demonstrate it. In experiments on femoral arteries, early application (at <6 h) of ibruprofen to the adventitia inhibited the VS probably by decreasing the periadventitial macrophage and granulocyte count (261). Older animal studies have also shown normalizing effects of ibuprofen and methylprednisolone on VS and CSF PG concentrations (262) and on vasoreactivity of cerebral arteries removed from animals subjected to SAH (263).…”
Section: -4 Nsaids and Glucocorticoidsmentioning
confidence: 99%
“…15,16 The basilar arteries were transected at the same point: two thirds of the distance from the proximal side to avoid the arterial branches. These sections were prepared over 200 m. Three cross-sections of each vessel were selected randomly for measurement.…”
Section: Histological Examination and Cross-sectional Area Measurementmentioning
confidence: 99%